2019
DOI: 10.3390/ijerph16071305
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of a Low-Intensity Cognitive Behavioral Therapy mHealth-Supported Intervention to Reduce Loneliness in Older People

Abstract: There is a high prevalence of loneliness among older people, especially in residential care settings. Loneliness is often accompanied by maladaptive cognitions which can affect the maintenance and establishment of meaningful social connections. This study implemented and evaluated a low-intensity Cognitive Behavior Therapy (LI-CBT) mHealth-supported intervention which targeted maladaptive cognitions in older people (≥60 years) experiencing loneliness. The three-month intervention using WhatsApp was implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 62 publications
(76 reference statements)
1
75
0
1
Order By: Relevance
“…With respect to our first research question, we found that the lack of social relationships and infrequent contacts have been the most commonly addressed challenges to overcome loneliness and social isolation. One prominent strategy has been to train older adults to use computers and Internet ( n = 16) [ 30 35 , 37 39 , 41 , 42 , 46 , 50 , 51 , 53 ], although few technologies built specifically for older adults implemented this strategy [ 35 , 46 , 54 ]. After an initial training period, older adults in these studies were left to put in practice the skills learned to get in touch with others, with the exception of a single intervention where participants received continuous training [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…With respect to our first research question, we found that the lack of social relationships and infrequent contacts have been the most commonly addressed challenges to overcome loneliness and social isolation. One prominent strategy has been to train older adults to use computers and Internet ( n = 16) [ 30 35 , 37 39 , 41 , 42 , 46 , 50 , 51 , 53 ], although few technologies built specifically for older adults implemented this strategy [ 35 , 46 , 54 ]. After an initial training period, older adults in these studies were left to put in practice the skills learned to get in touch with others, with the exception of a single intervention where participants received continuous training [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another strategy has been to ensure that the participants had someone to interact with ( n = 10). These would usually be health professionals responding or contacting participants with some frequency for checks or to facilitate the intervention [ 37 , 46 , 47 , 54 ] or other participants such as relatives who agreed to contact and support older adults during the study period [ 36 , 48 ]. Other interventions had volunteers making phone calls [ 43 ], trained interviewers having video chat conversations [ 44 ], and trained helpers linked to a virtual companion [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Silver Sneakers, a gym membership and exercise classes, was shown to increase physical activity and to reduce social isolation and loneliness compared to matched controls [ 37 ]. In addition, a pilot, m-Health intervention targeting maladaptive cognitions in elderly individuals who are experiencing loneliness reduced these symptoms over three months [ 38 ].…”
Section: Discussionmentioning
confidence: 99%